Severe bilateral bronchial stenosis with acute respiratory failure from granulomatosis with polyangiitis - Pattraporn Tajarernmuang (2018)
© 2016 Asian Pacific Society of Respirology. We report a 48-year-old female patient hospitalized with dyspnoea, wheezing, and respiratory failure due to bilateral main bronchial stenosis from granulomatosis with polyangiitis (GPA) involvement. By computed tomography imaging and flexible bronchoscopy, we measured the narrowest diameter at 2mm. The patient promptly recovered from respiratory failure after treatment with flexible bronchoscopic balloon dilatation (BBD) without any procedure-related adverse event. This report showed the benefits of urgent flexible BBD that was used as a rescue therapy in a GPA patient who presented life-threatening acute respiratory failure from severe bilateral bronchial stenosis.